2022
DOI: 10.3390/jcm11175099
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Procoagulant Microvesicles Are Elevated in Patients with Retinal Vein Occlusion (RVO)

Abstract: The etiopathogenesis of retinal vein occlusion (RVO) is multifactorial, and the contribution of platelets to RVO development has not been fully elucidated. We aimed to analyze platelet function in RVO patients (n = 35) and controls (n = 35). We found a higher (p < 0.05) level of soluble P-selectin in RVO group vs. controls. Additionally, in RVO patients, the concentration of platelet-derived microvesicles was higher (p < 0.05), and the difference between groups was deeper for the fraction of platelet-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…RVO is linked with atherosclerotic cardiovascular risk factors. Prior research has highlighted heightened expression of platelet-derived microvesicles and NETs-related markers in RVO patients, indicating functional activation of platelets and neutrophils [9]. RVO is influenced by the interplay of platelets, coagulation response, endothelial cells, and inflammatory response amidst blood flow abnormalities [10].…”
Section: Discussionmentioning
confidence: 99%
“…RVO is linked with atherosclerotic cardiovascular risk factors. Prior research has highlighted heightened expression of platelet-derived microvesicles and NETs-related markers in RVO patients, indicating functional activation of platelets and neutrophils [9]. RVO is influenced by the interplay of platelets, coagulation response, endothelial cells, and inflammatory response amidst blood flow abnormalities [10].…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] A recent study showed that although platelet count, MPV, PDW, plateletcrit, reticulated platelets, and platelet-lymphocyte ratio were similar to the control group in patients with RVO, the level of soluble P-selectin and concentration of platelet-derived procoagulant microvesicles was higher in patients with RVO in both BRVO and CRVO. [ 32 ] P-selectin is one of the best markers of platelet activation. Microvesicles are derived from membrane blebs of activated platelets and have pro-coagulant, anti-coagulant, pro-inflammatory, and angiogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…12 PMPs are derived from activated platelets and are the most abundant fraction of MPs in blood. 13 Recent evidence suggests that PMPs in blood circulation are associated with inflammation 14 and hypercoagulation, 15 thus being of pathophysiological importance in many diseases. 15,16 Siljander and colleagues reported that PMPs are associated with fibril formation.…”
Section: Introductionmentioning
confidence: 99%
“…Microparticles (MPs) in blood circulation are a heterogeneous population of small vesicles with an approximate 0.1–1.0 μm diameter, which can be generated by red blood cells, endothelial cells, white blood cells, and platelets 12 . PMPs are derived from activated platelets and are the most abundant fraction of MPs in blood 13 . Recent evidence suggests that PMPs in blood circulation are associated with inflammation 14 and hypercoagulation, 15 thus being of pathophysiological importance in many diseases 15,16 .…”
Section: Introductionmentioning
confidence: 99%